Human cytomegalovirus is present in the odontogenic epithelium of ameloblastoma - Mohammed Amjed Alsaegh; Sudhir Rama Varma; Alaa Muayad Altaie; Shengrong Zhu (Journal of Oral Microbiology, 2021)
Background: The factor behind the activation of the remnant odontogenic tissues and development of odontogenic cysts and tumors is poorly understood.This study aimed to investigate the presence of human cytomegalovirus (HCMV) in dentigerous cyst (DC), odontogenic keratocyst (OKC), and ameloblastoma (AB). Methods: The study included 41 samples, which distributed into DC (n=13), OKC (n=12), and AB (n=16). Conventional PCR assay and IHC analysis were used to detect the HCMV-DNA and HCMV glycoprotein B (HCMV-gB) respectively. Results: HCMV-DNA was detected in 10 samples (62.5%) of AB, four samples (30.8%) of DC, and three samples (25 %) of OKC respectively (χ2 test = 1.195, p= 0.247). Meanwhile, HCMV-gB was found in 12 (75%) of AB, in 2 (15.4%) of DC, and absent in OKC (0.0%) (χ2 test = 4.122, p= 0.042). Conclusions: The high prevalence of HCMV inside the odontogenic epithelium of AB could indicate a possible role of the virus in the oncogenesis and/or oncomodulation of the AB. Additionally, we recommend the IHC for the detection of HCMV in the odontogenic tumors like AB.